The Prevalence of Low Birth Weight and Its Correlation with Antenatal Care and Parental Smoking in Babylon Province (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Across sectional study was applied in Babylon teaching hospital for obstetric and children over six months period from April 2020 to September 2020 the study was done on 754 full term live birth neonateThe birth wight and gestational age was taken for all newborn. The gestational age was calculated by last menstrual period and ultrasound examination and a new Ballard score. Full term is considered when the gestational age is ≥ 37 weeksPremature and infants with birth defects were excluded from the studyQuestionnaire was taken from mother whither attend ANC (antenatal care) or not and whither mother and father are smoker or not.The total number of low births weight was 69 from the total number full term which are 754 with a percentage of 9.2% and the number of large gestational age is 22 with a percentage of 2.9% . there is significant relationship between antenatal care and low birth weight with P-value